THE HARMONIOUS, ODD HARMONIOUS, AND EVEN HARMONIOUS LABELING - Lasim, Ahmad; Halikin, Ikhsanul; Wijaya, Kristiana (PATTIMURA UNIVERSITY, 2022)
Suppose is a simple and connected graph with edges. A harmonious labeling on a graph is an injective function so that there exists a bijective function where for each An odd harmonious labeling on a graph is an injective function from to non-negative integer set less than so that there is a function where for every An even harmonious labeling on a graph is an injective function so that there is a bijective function where for each . In this paper, we discuss how to build new labeling (harmonious, odd harmonious, even harmonious) based on the existing labeling (harmonious, odd harmonious, even harmonious)